Production of new soap from recyclable material - Nadya Orsela Andico (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Recycle is known as the process of converting waste materials into new product that potentially useful. In this project, new soap is produced from disposed hotel bar soap to reduce the waste from hotel. Water content, glycerin content, and salt content are the parameters studied in this recycling process. Moisture content was analyzed as the main characteristic of soaps. The Response Surface Methodology (RSM) approach was applied to get the optimum condition for the parameters to produce soap within the moisture content allowable range which is 15%-30%. Only 3 out of 20 experiments produced out-of-range moisture content which is experiment number 11, 5.09%, number 5, 38.32%, and number 14, 35.27%. The most important reasons are glycerin content and salt content which has the p-value of 0.0096 and 0.0116 respectively. Those values indicate that glycerin and salt content are the parameters which are significant. The techno-economic study revealed for a bar soap of 100 grams, the production cost is RM 1.70. It was concluded that the production of new soap from disposed bar soap was successfully accomplished by optimizing the three parameters. The result on techno-economic study indicates that it is necessary for future study to constrict the production cost of soap, so that the production will be less costly.